2012
DOI: 10.1063/1.4731271
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar inverters using SnO thin-film transistors with balanced electron and hole mobilities

Abstract: Ambipolar thin film transistors have attracted increasing research interests due to their promising applications in complementary logic circuits and the dissipative charge transporting devices. Here, we report the fabrication of an ambipolar transistor using tin mono-oxide (SnO) as a channel, which possesses balanced electron and hole field-effect mobilities. A complementary metal oxide semiconductor-like inverter using the SnO dual operation transistors is demonstrated with a maximum gain up to 30 and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 25 publications
2
109
1
Order By: Relevance
“…While for V dd at 3.0 V, the voltage gain arrives at $20. It was reported that the depletion loaded inverter exhibited a voltage gain of $20 at V dd of 9 V, 26 while the complementary inverter exhibits voltage gain of $20 at V dd of 30 V. 27 In our case, a high voltage gain of $20 could be obtained at a low supply voltage of only 3 V, which indicates the high potential for the proposed inverter in portable applications. Furthermore, the transition width values are also extracted from VTCs, as shown in Fig.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…While for V dd at 3.0 V, the voltage gain arrives at $20. It was reported that the depletion loaded inverter exhibited a voltage gain of $20 at V dd of 9 V, 26 while the complementary inverter exhibits voltage gain of $20 at V dd of 30 V. 27 In our case, a high voltage gain of $20 could be obtained at a low supply voltage of only 3 V, which indicates the high potential for the proposed inverter in portable applications. Furthermore, the transition width values are also extracted from VTCs, as shown in Fig.…”
Section: Resultsmentioning
confidence: 50%
“…It should be noted here that the transition width is below 0.5 V. Such value is also much lower than that for the reported inverters. 26,27 The narrow transition width could be expected to improve the response characteristics of logic circuit. …”
Section: Resultsmentioning
confidence: 99%
“…To realize complementary inverters, one can either combine an n-type TFT and a p-type TFT or use two ambipolar TFTs. A rail-to-rail output voltage behavior can be easily achieved in the former but hard to achieve in latter case because neither of the two ambipolar TFTs can be fully switched off [8,9,10,11]. The static current will also result in a static power consumption, which may be an issue in the case of large scale integration.…”
Section: Introductionmentioning
confidence: 99%
“…Cao and co-workers [83][84][85]88,89 favour a two-step process involving the electron beam evaporation (EBE) of SnO 2 on p-type silica, followed by thermal annealing at temperatures between 300 and 600 C. Conversely, the epitaxial process , 90 respectively. However, unlike the latter approaches, EBE and PLD are suggested to be less amenable to large-scale device production.…”
Section: 85mentioning
confidence: 99%